(3cGed GdJhGQjNs - (3GdTjHGfqj GdLRQj, CHh GdMSf (B, (3GHf GdCKjQ, YR GdOjf, Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO, J (B630 (3g`s
(3ChdgG (B:s
(3HgOeg ef MjWGfgG hSGQ eQhGf Edi MUf GdcGed MfbG Ydi ef ajg aMUQge hCfRdge Ydi Mceg, aeKd Hge hCNPge Cgd GdQbI aOGhhG LQGMGJge agdc HYVge hHbj CcKQge, hcGfJ YOJge fMhG ef KdGKeGFIs
(3BNQgG (B:s
(3PcQ CNHGQ GdbQGeWI hcGf gPG GdbQeWj jRYe Cfg EPG CTGQ HjOg Edi LgI ef GdJj ajgG eMGQHhg GfgRehG hdeG bJd jMji GdeYQha HGdTjN hbJd CUMGHg, GLJeY ef Hbj efge Ydi CNjg GdMSjf, hSei faSg s
(3JHUQI GdYfhGf (B:s
(3GdcGed aj GdJGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\331s
(3cTa GdXfhf (B2\1380s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs